Influence of strain rate on the mechanical behavior of dry and hydrated chitosan-based dense materials for bioabsorbable implant applications. (April 2021) - Figueiredo, Lígia; Gregório, Afonso V.L.; Rodrigues, Alexandra; Rosa, Pedro A.R.
Abstract: Chitosan has generated enormous interest in the scientific community because of its distinctive biological and physicochemical properties, which allow new advanced structures and applications. Porous chitosan scaffolds have been extensively studied and explored in bone generation, however it is still a challenge to obtain bioabsorbable orthopedic implants that involves pure 3D dense chitosan geometries due to the inherent difficulties in producing and shaping such structures. In this work, chitosan was blended with 10% glycerol and 10% glycerol + 10% biphasic mixture of calcium phosphate (70% hydroxyapatite with 30% β-tricalcium phosphate) to produce dense chitosan-based blocks, which were then shaped into rods. The introduction of plasticizer aimed to improve the materials ductility while the ceramic particles were used to increase stiffness and strength. The mechanical behavior of the two chitosan-based compositions was evaluated by uniaxial compression tests using a customized split-Hopkinson pressure bar (SHPB). The specimens were analysed in quasi-static conditions (less than 0.1 s − 1 ) and medium strain rate conditions (200–800 s − 1 ), both in dry state and in different hydrated conditions, in the latter case to approximate the in vivo implant conditions. The results showed promising results for the intended application. The chitosan blends present excellent ductility with an elastic perfect-plastic behavior in quasi-static conditions, with yield stresses around 40 MPa for the dry state, with a decay for 3 MPa after 48h hydration. An empirical model was proposed to describe the flow stress curves, with a good agreement with the experimental data, allowing future modelling of this material behavior.